2014
DOI: 10.5798/diclemedj.0921.2014.04.0506
|View full text |Cite
|
Sign up to set email alerts
|

Smoking habits of factory workers and their thoughts about cessation of smoking

Abstract: Objective: The aim of this study was to determine smoking habits, levels of nicotine dependence, thoughts about smoking and smoking cessation of workers.Methods: This descriptive and cross-sectional study was conducted by volunteer 200 workers from cement and sugar factories in 2014 Çorum. The data was collected through a 40-item questionnaire form questioning smoking habits, thoughts about smoking and cessation of workers. To determine nicotine dependence Fagerstrom Nicotine Dependence Test was used.Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
2
0
0
Order By: Relevance
“…It was also observed that participants who smoked or chewed tobacco for < 10 years are more likely ready to quit the habit. However, most of the participants who never quit the habit were using tobacco for more than decade, which can be correlated with the study done by Pimple et al 21 and Yılmazel et al 5 On the contrary, mean frequency of tobacco use among both the groups was more than 10 times per day, which was found similar to the study conducted by Pimple et al 21 and Verra et al 34 The majority of participants in quitter and never quit groups consume smokeless form of tobacco (232 [93.5]; 288 [73.5]) respectively, which is similar to Desai et al, 35 Kumar et al, 27 and Agrawal et al 36 The authors reported that the prevalence of a smokeless form of tobacco was most common in Maharashtra, and it is more commonly seen among the lower socioeconomic class, whereas Agrawal et al 36 reported that the prevalence of tobacco use was more in an urban area. Furthermore, it has been observed that majority of participants in both the groups [208 (83.9); 304 (77.6)] smoked or chewed tobacco at workplaces.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…It was also observed that participants who smoked or chewed tobacco for < 10 years are more likely ready to quit the habit. However, most of the participants who never quit the habit were using tobacco for more than decade, which can be correlated with the study done by Pimple et al 21 and Yılmazel et al 5 On the contrary, mean frequency of tobacco use among both the groups was more than 10 times per day, which was found similar to the study conducted by Pimple et al 21 and Verra et al 34 The majority of participants in quitter and never quit groups consume smokeless form of tobacco (232 [93.5]; 288 [73.5]) respectively, which is similar to Desai et al, 35 Kumar et al, 27 and Agrawal et al 36 The authors reported that the prevalence of a smokeless form of tobacco was most common in Maharashtra, and it is more commonly seen among the lower socioeconomic class, whereas Agrawal et al 36 reported that the prevalence of tobacco use was more in an urban area. Furthermore, it has been observed that majority of participants in both the groups [208 (83.9); 304 (77.6)] smoked or chewed tobacco at workplaces.…”
Section: Discussionsupporting
confidence: 84%
“…In the present study, the mean age among quitters was significantly low compared with those who never quit tobacco habit. This age group was in line with the study done in Mumbai by Pimpale et al 21 Here, the effect of behavioral counseling was tested among the factory workers, whereas it was quite different from the studies of workplace cessation programs carried out by Eriksen, 22 Cruse et al, 23 Chong et al, 24 and Yılmazel et al 5 This contrast was found because those studies were conducted among blue-and white-collar workers, and our study engaged the factory workers in skilled, unskilled, or semiskilled work categories and of low socioeconomic status. The majority of the participants in both the groups were male and literate, but those who never quit were either less educated or illiterate.…”
Section: Discussionsupporting
confidence: 64%